Komunikasi Interpersonal Customer Service Lotte Grosir dalam Melayani Pelanggan di Kota Samarinda - Pradela Salsabila Sari; Ainun Ni'Matu Rohmah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Interpersonal communication plays an important role in a company, one of which is retail, the quality of good interpersonal communication needs to be mastered by customer service because it deals directly with customers, the quality of interpersonal communication is needed to create good service for customers. The purpose of this study was to determine the interpersonal communication process of Lotte Grosir's customer service in serving customers in Samarinda City. The research method used is a qualitative method. Data collection techniques include interviews, observation and documentation. The informants in this study consisted of 3 customer service people, 1 guard manager and 2 customers. The results of this study indicate that there are 6 elements found in the field, namely self-introduction and other individuals from customer service openness to customers and customer service digging into customer backgrounds to reduce uncertainty to customers. Knowing the situation can be seen from the way customer service listens to complaints experienced by customers before providing solutions. Creating and maintaining meaningful relationships is evident in customer service. Providing service to customers in a friendly and courteous manner, not hurting customer feelings, giving trust to customers. Persuasion is seen when customer service provides options for exchanging goods before a refund is made if there is a discrepancy with the customer. Relaxed interactions can be seen from the way customer service makes jokes to customers, but one customer service that lacks initiative tends to wait for customers who ask questions. Helping seen from customer service helps reduce cognitive and behavioral uncertainty in customers in making decisions if customers feel unsure about their choices.